If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4x*3+8x=0
We simplify the equation to the form, which is simple to understand
-4x*3+8x=0
Simplifying:
-12x+8x=0
We move all terms containing x to the left and all other terms to the right.
-12x+8x=0
We simplify left and right side of the equation.
-4x=0
We divide both sides of the equation by -4 to get x.
x=-0
| (2x-3)-(-x+6)= | | -31-4x=5-10 | | 2x^6+3= | | 30+7y=-2y-6 | | 3x+32+(-24x)=6+-36x-6+-16x | | 6(4x-y)+5= | | 14x+6x=20 | | 6x^3-13x^2+9x-2=0 | | 4x(2)=32 | | (5x-3)*(-2x-5)=0 | | (2x-3)(x)=54 | | 3a+2=a+8 | | [(8x+21)+(5x+63)]+2y=360 | | (8x+21)+(5x+63)+2y=360 | | 6(x+2)(x-4)= | | 8x+21=5x+63 | | (n+2)*8=24 | | (n-5)*5=10 | | 10x-9=101 | | 30+63+2x+7=180 | | x^2+7+1=0 | | 2(3a+b)-6(2a-3b)= | | (n+1)*9=27q | | (n-4)*6=12 | | 148-2x=25x+19 | | 7-9x=83-23x | | x*x+7x=12 | | a*8+6=3 | | 8(x+2)=4(x+10) | | 4x-5=72-7x | | 152-10x=9x+19 | | 8x+5=3x+0 |